Wettability and Water Uptake Improvement in Plasma-Treated Alfalfa Seeds - Matej Holc; Peter Gselman; Gregor Primc; Alenka Vesel; Miran Mozetič; Nina Recek (Agriculture, 2022)
The cultivation of alfalfa (Medicago sativa L.), a forage crop grown worldwide, is negatively affected by hard seed presence. We show that treatment of alfalfa seeds with an inductively coupled radio frequency oxygen plasma improves their surface hydrophilicity, as determined by water contact angle (WCA) measurements and water uptake. Furthermore, we see that these effects are mediated by functionalization and etching of the alfalfa seed surface. Surface chemistry is analyzed by X-ray photoelectron spectroscopy (XPS), while morphology is viewed using scanning electron microscopy (SEM). Plasma produces effective alfalfa seed hydrophilization with a variety of treatment parameters. With its potential for fine-tuning, plasma modification of seed wettability shows promise for introduction into agricultural practice.